Wear resistance of vanadium-niobium carbide layers grown via TRD (2015)
Nb-V complex carbide coatings were produced on AISI D2 steel substrates using the thermo-reactive diffusion (TRD) process in order to improve the surface hardness and wear resistance of this tool steel. The carbide coating treatment was performed using molten borax with added ferroniobium, ferrovanadium, and aluminum at temperatures of 1223, 1293, and 1363 K for 2, 3, 4, and 5 h. The coating layers were characterized with scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy-dispersive X-ray spectroscopy (EDS). The growth rates of the coatings were studied, and a kinetic model of the layer thickness was constructed as a function of the time and temperature treatment. The hardness and friction coefficient (COF) of the coatings was measured through nanoindentation and pin on disk test respectively. The carbide layers had a homogeneous thickness and a hardness of 37.63 GPa, which is close to values obtained in superhard materials, and the COF was in the range of 0,3 for the coated steels.